Características clínico-epidemiológicas y laboratoriales de pacientes adultos hospitalizados con diagnóstico de novo de neoplasias hematológicas - Paz Temoche, Romario Yordano (2017)
A descriptive, cross-sectional and retrospective study was carried out at Hospital Belén de Trujillo between January 2010 and December 2014 with adult patients, evaluated in hospitalization with novo diagnosis of Hematologic Neoplasia by anatomopathology, being characterized both clinically and epidemiologically as well as laboratorially of the review of Clinical Histories. RESULTS: We found 88 patients with a diagnosis of hematologic malignancy. In addition, 33% of the cases were diagnosed as Myeloid Leukemia, followed by Non-Hodgkin's Lymphoma 29.5% and Lymphoid Leukemia 19.3%. The mean age at diagnosis was 50.68 ± 21.17 years (range 18 - 94 years). We found 46 male patients and 42 female patients, the M: F ratio being 1.1: 1, and male predominance was found for most Hematologic Neoplasms. 59.7% of cases came from Trujillo. The most frequent symptom evaluated was hyporexia (74.1%) and pallor (82%), the most frequent sign. Hematologic neoplasms were found to have an average disease time of 166.5 ± 391 days (range 3 to 2880 days). Regarding the laboratory characteristics, bicytopenia was found in 28 cases (33.3%) and pancytopenia in 20 cases (23.8%) of the total hematological malignancies. CONCLUSIONS: The most frequent Hematologic Neoplasia was Myeloid Leukemia. We found a higher prevalence of males. The mean age at diagnosis was 50.68 years. The highest proportion of cases came from Trujillo. The most common symptom and sign were hyporexia and pallor, respectively. The majority of cases presented with bicytopenia or pancytopenia